Pengaruh Kualitas Pelayanan Petugas Check-In Counter KNP Kokapura terhadap Kepuasan Penumpang Maskapai Wings Air di Bandar Udara Internasional Jendral Ahmad Yani Semarang - Nur Alif Kurniawan; Eny Sri Haryati (MES Bogor, 2024)
General Ahmad Yani Semarang International Airport (SRG) is an airport located in the city of Semarang. KPN Kokapura Ahmad Yani must pay attention to services and facilities in the Check-In Counter area because they can affect passenger satisfaction. The main objectives of this research are as follows: 1) to find out whether there is an influence on the service quality of KPN Kokapura Check-In Counter officers on passenger satisfaction with Wings Air at Jendral Ahmad Yani International Airport Semarang and 2) to find out how much influence the Service Quality of Check-In Officers has. KPN Kokapura Counter on Wings Air Passenger Satisfaction at Jendral Ahmad Yani International Airport, Semarang. This research method uses quantitative methods. The number of samples in this research was 100 respondents. The respondents in this research were Wings Air passengers at Ahmad Yani International Airport, Semarang. The sampling technique in this research uses a Non-Probability Sampling technique with a Purposive Sampling approach, namely a sampling technique based on certain criteria that will be used as samples. Data analysis techniques use data management and drawing conclusions. The research results show that the significant value is 0.000<0.05 and the calculated t value is 3.604>t table value 1.660, which means that there is a positive influence on the quality of the KPN Kokapura Check-In Counter service on the satisfaction of Wings Air airline passengers at Jendral Ahmad Yani International Airport, Semarang. Based on the R square (R2) value of 0.117. shows that the Check-In Counter officer's service quality variable has an effect of 11.7% on passenger satisfaction. Meanwhile, 88.7% is explained by variables other than the independent variables in the research.